Review on phenotypic characterization and breeding objective traits of indigenous chicken in Ethiopia - Sufiyan Abdi Musa; Kefelegn Kebede; Debeli Tadesse (International Journal of Veterinary Science and Research - Peertechz Publications, 2023)
For local chicken ecotypes, knowledge of the distribution of genetic diversity will be useful for optimizing conservation and utilization strategies. In Ethiopia, rural chickens are found in huge numbers distributed across different agroecological zones under a traditional family-based scavenging management system. However, due to the prevalence of diseases and predators, low genetic potentials, feed shortage, and limited feed resources, constraints related to the institutional, infrastructural, socio-economic, and economic contribution of local chickens are not proportional to their huge number. Therefore, the aim of this review was to describe the production system, phenotypic characterization, and breeding objective traits of local chicken ecotypes. Overall desired traits by farmers are body weight, comb type, breeding ability, plumage color, body conformation, egg number, and size, adaptive trait, and mothering ability. Generally, these traits are considered important for selecting chicken in a market for meat and egg consumption and for breeding purposes in Ethiopia. Therefore, these preference traits and breeding objectives of farmers are important to improve the genetic part of chickens in Ethiopia.